The Effect of Business Capital Financing Utilization on MSME Development: The Moderating Role of Financial Literacy (Evidence from MSMEs in East Kota District, Gorontalo City Financed by Amartha Point) - Anastasya Kandow; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (International journal of technology and education research, 2026)
This study aims to analyze the effect of business capital financing utilization on the development of micro, small, and medium enterprises (MSMEs) and to examine the role of financial literacy as a moderating variable. The research employed a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 96 MSME owners who received financing from Amartha in East City District, Gorontalo City. Data analysis was conducted using Moderated Regression Analysis with the assistance of SmartPLS software. The results indicate that the utilization of business capital financing has a positive effect on MSME development. However, the moderation test results show that financial literacy does not moderate the effect of business capital financing utilization on MSME development. The t-statistic value of 0.712, which is smaller than the significance threshold of 1.96, and a significance value of 0.477, which is greater than 0.05, indicate that financial literacy does not function as a moderator. These findings suggest that improvements in MSME development are primarily influenced by the amount and form of financing utilization itself rather than by the financial literacy level of business actors.